Síntese de complexos de cobre(II) com ligantes triazenido 4- halofenil substituídos e investigação de interações secundárias entre átomos de halogênio - Santos, Felipe Boz (2014)
This work deals with the synthesis and characterization of four copper(II) complexes including halophenyl-substituted triazenido and 2,2'-bipyridine ligands. The triazenido ligands were chosen strategically in view of the investigation of supramolecular self-assemblies via secondary F···F, Cl···Cl, Br···Br and I···I interactions. In addition diverse geometric parameters were investigated by single crystal structure analysis of the compounds including discussions related to properties of the ligands in view of the coordination geometry of cooper(II). In special, the positional disorder of halogen substituents, as well as, elimination of electron densities related to solvate molecules showing high disordering were treated. Beside the single crystal structure analysis, the complexes were also characterized by elemental analysis, UV-vis and infrared spectroscopies. The in the follow investigated complexes were obtained in organic solvents starting from the previously synthetized ligands 1,3-Bis(4-fluorophenyl)triazene, 1,3- Bis(4-chlorophenyl)triazene, 1,3-Bis(4-bromophenyl)triazene and, 1,3-Bis(4- iodophenyl)triazene: cis-Bis[1,3-bis(4-fluorophenyl)triazenide-κ 2N1,N3](2,2’-bipyridine- κ 2N1,N1’)copper(II), cis-Bis[1,3-bis(4-chlorophenyl)triazenide-κ 2N1,N3]-(2,2’-bypiridine- κ 2N1,N1’)copper(II), cis-Bis[1,3-bis(4-bromophenyl)triazenide-κ 2N1,N3]-(2,2’- bypiridine-κ 2N1,N1’)copper(II) and, cis-Bis[1,3-bis(4-iodophenyl)triazenide-κ 2N1,N3]- (2,2’-bypiridine-κ 2N1,N1’)copper(II).